Life quantity, life quality and longevity: An intertemporal social evaluation framework - Jean-Yves Duclos; Bouba Housseini (Fondation pour les études et recherches sur le développement international (FERDI), 2013)
The evaluation of development processes and of public policies often involves comparisons of social states in which populations differ in size and longevity. This requires social evaluation principles to be sensitive to both the number and the length of lives. This paper explores the use of axiomatic and welfarist principles to assess social welfare in that framework. It attempts to overcome some of the limits of existing methods in the literature, in particular by avoiding a temporal repugnant conclusion, by neither penalizing nor favoring life fragmentation, and by satisfying critical-level temporal consistency. It does this by characterizing a critical-level lifetime utility function that values life periodically. To address some of the controversies on discounting utilities across time, two alternative versions of the function are developed, one with discounting and one without.
Keywords: C02; D31; D63; I31; J17; 330